If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -9 = x + -2 Reorder the terms: -9 + 8x = x + -2 Reorder the terms: -9 + 8x = -2 + x Solving -9 + 8x = -2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -9 + 8x + -1x = -2 + x + -1x Combine like terms: 8x + -1x = 7x -9 + 7x = -2 + x + -1x Combine like terms: x + -1x = 0 -9 + 7x = -2 + 0 -9 + 7x = -2 Add '9' to each side of the equation. -9 + 9 + 7x = -2 + 9 Combine like terms: -9 + 9 = 0 0 + 7x = -2 + 9 7x = -2 + 9 Combine like terms: -2 + 9 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| 3x+-1y=2 | | 22+14z= | | 13p-6=7p+12 | | 3a+7b=0 | | (2.9)(7)=(4)(X) | | (10+x)(10+(x+5))=300 | | xsquared+12=373 | | h=-16t^2+39t+20 | | 10y=5x+4 | | xsquared-32=81 | | 3a+5b=8 | | X-2(x+7)=4(2x-1) | | 7ysqared=112 | | 100+x=12x+1 | | 3squared+24=88 | | 6+18y= | | 12(x+8)=10x+16 | | 2x-4n-8=0 | | 8x+5=10x-5 | | 0.66x-5=2x | | 3(x-4)=-4+44 | | 15+3n=27 | | -6=-4-2x | | -8x(x+1)=4(x-11) | | 4x+1=5j-1 | | y=x^2+60x-300 | | 4(3+3x)-2=70 | | x+(x+5)=69 | | 22x=25x-6 | | 6(2n-1)=2(5n-3)+4n | | 9y+1=8y-2 | | (u-7)(u+1)= |